THE EVENT OF SEPTEMBER 11TH IN AMERICAN AND SYRIAN WRITTEN MEDIA DISCOURSE - Benham, Biook; Khodadust, Mohammad Reza (Universitas Pendidikan Indonesia, 2012)
Abstract: Aiming at highlighting the important role of written media discourse in implicit transfer of the dominant ideology of discourse context, the present data-driven paper demonstrates how the lexical features of repetition and synonymy as well as the structural and thematic features of passivisation, nominalization and predicated theme were utilized by the discourse producers of the data to mediate between their own underlying ideology and the target readers' understanding of the event of September 11th 2001. Through a comparative statistical analysis of the written media discourse of the data for the study written in two ideologically opposing contexts of Syria and America, we have tried to explicate how the discourse producers utilized various lexical and thematic strategies to produce different impressions of the event and implicitly force the underlying ideology on the readers. Keywords: September 11th 2001, thematization, passivisation, nominalization, synonymy, CDA